Sejarah Pemeliharaan Hadis Nabi Pra-Kodifikasi: Studi Kitab As-Sunnah Qabla At-Tadwin Karya Muhammad ‘Ajaj Al-Khatib (W. 1443/2021) - Abdul Majid (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
The history of hadith, such as regarding the issue of its codification, which has an important role, position, or contribution in the development of Islamic historiography, has left various problems of interpretation that are not clear, complicated, and problematic, thus triggering scholars to respond. One of them is Muhammad ‘Ajaj al-Khatib through his work as-Sunnah Qabla at-Tadwin. However, ‘Ajaj’s thoughts on the history of hadith in his book are still not explained analytically. This study aims to fill that gap. This study is a literature study of the work of ‘Ajaj, as-Sunnah Qabla at-Tadwin, which is equipped with various relevant secondary sources. The result is that ‘Ajaj’s thoughts found in his book as-Sunnah Qabla at-Tadwin are a response to the accusations by skeptics of the Prophet's hadith which are considered problematic in their historicity and authenticity. ‘Ajaj’s response to this topic aims not only to strengthen Muslim’s belief in the authenticity of the Prophet’s traditions but also to enlighten Muslim’s understanding of the history of the Prophet’s traditions and affirm the view that the Prophet's traditions have been preserved since the time of the Prophet. For ‘Ajaj, the hadith of the Prophet SAW from the beginning has been guaranteed to be authenticated. Because, since the time of the Prophet, hadith has been studied, taught, and maintained seriously and strictly. This is because so much attention has been paid to the hadith as the second source of Islamic teachings, and the consequences for those who deny it are so heavy.